'I will choose when to test, where I want to test': investigating young people's preferences for HIV self-testing in Malawi and Zimbabwe. (1st July 2017) - Indravudh, Pitchaya P.; Sibanda, Euphemia L.; d'Elbée, Marc; Kumwenda, Moses K.; Ringwald, Beate; Maringwa, Galven; Simwinga, Musonda; Nyirenda, Lot J.; Johnson, Cheryl C.; Hatzold, Karin; Terris-Prestholt, Fern; Taegtmeyer, Miriam
Abstract : Objectives: The current study identifies young people's preferences for HIV self-testing (HIVST) delivery, determines the relative strength of preferences and explores underlying behaviors and perceptions to inform youth-friendly services in southern Africa. Design: A mixed methods design was adopted in Malawi and Zimbabwe and includes focus group discussions, in-depth interviews and discrete choice experiments. Methods: The current study was conducted during the formative phase of cluster-randomized trials of oral-fluid HIVST distribution. Young people aged 16–25 years were purposively selected for in-depth interviews ( n  = 15) in Malawi and 12 focus group discussions ( n  = 107) across countries. Representative samples of young people in both countries ( n  = 341) were administered discrete choice experiments on HIVST delivery, with data analyzed to estimate relative preferences. The qualitative results provided additional depth and were triangulated with the quantitative findings. Results: There was strong concordance across methods and countries based on the three triangulation parameters: product, provider and service characteristics. HIVST was highly accepted by young people, if provided at no or very low cost. Young people expressed mixed views on oral-fluid tests, weighing perceived benefits with accuracy concerns. There was an expressed lack of trust in health providers and preference for lay community distributors. HIVST addressed youth-specific barriers to standard HIV testing, with home-based distribution considered convenient. Issues of autonomy, control, respect and confidentiality emerged as key qualitative themes. Conclusion: HIVST services can be optimized to reach young people if products are provided through home-based distribution and at low prices, with respect for them as autonomous individuals. Abstract : Supplemental Digital Content is available in the text